2013
DOI: 10.1186/1743-422x-10-322
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of 5-lipoxygenase activity and expression during dengue serotype-2 infection

Abstract: BackgroundLeukotriene B4, a 5-lipoxygenase product of arachidonic acid with potent chemotactic effects on neutrophils, has not been assessed in dengue patients. In this study, plasma leukotriene B4 and serum high-sensitivity C-reactive protein levels were determined in adult patients during the febrile, convalescent and defervescent stages of dengue serotype-2 (DENV-2) infection, and compared with those of age--matched healthy and non-dengue febrile subjects. In vitro studies were performed to examine the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
1
8
1
1
Order By: Relevance
“…reported that in rat aortic vascular smooth muscle cells, angiotensin II involves 5‐LOX to produce leukotriene B 4 from arachidonic acid 2.5 min after treatment; whereas, inhibition of 5‐LOX by MK886 attenuates angiotensin II‐induced leukotriene B 4 production, suggesting that 5‐LOX is involved early in the production of leukotriene B 4. In contrast, exposure of human neutrophils to dengue virus induces 5‐LOX expression 7 h after exposure to dengue virus, and augments leukotriene B 4 production . In our current study, dexmedetomidine‐induced contraction involving 5‐LOX was rather acute; 5‐LOX and COX‐2 expression was upregulated at 10–60 min and 10–20 min after pretreatment with dexmedetomidine, respectively.…”
Section: Discussioncontrasting
confidence: 50%
“…reported that in rat aortic vascular smooth muscle cells, angiotensin II involves 5‐LOX to produce leukotriene B 4 from arachidonic acid 2.5 min after treatment; whereas, inhibition of 5‐LOX by MK886 attenuates angiotensin II‐induced leukotriene B 4 production, suggesting that 5‐LOX is involved early in the production of leukotriene B 4. In contrast, exposure of human neutrophils to dengue virus induces 5‐LOX expression 7 h after exposure to dengue virus, and augments leukotriene B 4 production . In our current study, dexmedetomidine‐induced contraction involving 5‐LOX was rather acute; 5‐LOX and COX‐2 expression was upregulated at 10–60 min and 10–20 min after pretreatment with dexmedetomidine, respectively.…”
Section: Discussioncontrasting
confidence: 50%
“…In the presence of MK886 ( ALOX5 activating protein antagonist) the increase in leukotriene B4 biosynthesis is reduced indicating the relevance of the ALOX5 pathway in dengue virus infection. Consistent with this conclusion is the observation that in vivo plasma levels of leukotriene B4 were significantly elevated during the febrile stages of dengue infections [389]. …”
Section: Lipoxygenase Isoforms In Infectious Diseasessupporting
confidence: 55%
“…When human neutrophils are infected in vitro with the dengue virus (DENV-2), ALOX5 expression is upregulated and the cells biosynthesize significantly more leukotriene B4 [389]. In the presence of MK886 ( ALOX5 activating protein antagonist) the increase in leukotriene B4 biosynthesis is reduced indicating the relevance of the ALOX5 pathway in dengue virus infection.…”
Section: Lipoxygenase Isoforms In Infectious Diseasesmentioning
confidence: 99%
“…Apart from being pro‐inflammatory mediators and potent chemoattractants, some are also known to increase vascular permeability and induce vascular leak . Increased activity of LTB4 has been observed in patients with acute dengue viral infection, and exposure of neutrophils to the DENV induced the production of LTB4 . In addition, in experimental dengue mouse models, treatment with leukotriene receptor antagonists resulted in a significant reduction in plasma leakage in dengue‐infected mice, suggesting that leukotrienes may be playing an important role in fluid leakage in dengue.…”
Section: Introductionmentioning
confidence: 99%